2017
DOI: 10.1515/med-2017-0030
|View full text |Cite
|
Sign up to set email alerts
|

Causal neuro-immune relationships at patients with chronic pyelonephritis and cholecystitis. Correlations between parameters EEG, HRV and white blood cell count

Abstract: AbstractWe aim to analyze in bounds KJ Tracey’s immunological homunculus conception the relationships between parameters of electroencephalogram (EEG) and heart rate variability (HRV), on the one hand, and the parameters of bhite blood cell count, on the other hand.MethodsIn basal conditions in 23 men, patients with chronic pyelonephritis and cholecystitis in remission, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 55 publications
(82 reference statements)
7
58
0
Order By: Relevance
“…The WBC count, for instance, contains information on adaptability and health. 40 It has also been reported that an increase in sympathetic tone in female rats increases lymphocyte counts and decreases monocyte counts 39 which was observed in this study. 40 It has also been reported that an increase in sympathetic tone in female rats increases lymphocyte counts and decreases monocyte counts 39 which was observed in this study.…”
Section: Haematological Analysissupporting
confidence: 76%
See 1 more Smart Citation
“…The WBC count, for instance, contains information on adaptability and health. 40 It has also been reported that an increase in sympathetic tone in female rats increases lymphocyte counts and decreases monocyte counts 39 which was observed in this study. 40 It has also been reported that an increase in sympathetic tone in female rats increases lymphocyte counts and decreases monocyte counts 39 which was observed in this study.…”
Section: Haematological Analysissupporting
confidence: 76%
“…The WBC count, for instance, contains information on adaptability and health. 39 Presence of abundant numbers of WBC confirms the presence of infection. 40 It has also been reported that an increase in sympathetic tone in female rats increases lymphocyte counts and decreases monocyte counts 39 which was observed in this study.…”
Section: Haematological Analysismentioning
confidence: 97%
“…About the state of the phagocytic function of neutrophils (microphages) and monocytes (macrophages) were judged by the phagocytic index, the microbial count and the killing index for Staphylococcus aureus (ATCC N25423 F49) [5,20,25].…”
Section: Methodsmentioning
confidence: 99%
“…
Experimental and clinical physiology and biochemistry, ECPB 2019, 2(86): 11-23. https://doi.org/ hand, and HRV and EEG, on the other hand, as well as between changes in the immune and neural parameters caused by balneotherapy [15,16,17,18,19,20]. Hence, a hypothesis that, for the same states of the autonomic nervous system, the differences in immune responses to chronic stress were due to the features of the EEG.
…”
mentioning
confidence: 99%
“…Normal values are borrowed from the instructions for devices as well as databases of the Truskavets' Scientific School [15,16,17,18,19,20].…”
mentioning
confidence: 99%